UPAYA INTERNASIONALISASI RENMINBI MELALUI PROPOSAL PETROYUAN CHINA KE GCC - Agus Nilmada Azmi; Aunurrofiq Aunurrofiq; Reina Permata Hadikusuma; Tasya Naura Arivia (Penerbit Media Wawasan Ilmu, 2022)
China's initiative in the Internationalization of Renminbi international trade transactions carried out by the Government of China by the launch of a pilot project, by starting to use yuan in international transaction activities in China's five main regions, Shanghai, Guangzhou, Shenzhen, Zhuhai and Dongguan. China also sees countries in the Middle East as a strategic position in establishing cooperation, especially in the oil and gas sector. From establishing cooperation through the GCC, China also cooperates with member countries, Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates. Arab. The petroyuan has the opportunity to take a more prominent role in international trade to take over the petrodollar, given the weight of China's oil imports is increasing and imports from the United States are decreasing. In analyzing the internationalization of Renminbi, the author uses an approach through the theory of foreign policy and national interest. The author uses a qualitative research method, by taking and collecting various sources of literature as a reference.